Managerial autonomy and control at a retail chain store. (2019) - Hiltunen, Esa; Julkunen, Saara; Kantanen, Teuvo
This study examines autonomy and control in department managers' working lives at a large grocery retail unit of a hypermarket chain in Finland. The study analyses the narratives of two departmental managers in similar work situations: women with high self-efficacy and internal loci of control (LOCs), but very different personalities. To study autonomy, control and retail managers' internal LOCs in relation to retail work characteristics in detail, the job characteristics model is applied. The narratives of the studied department managers show how different personalities and behaviours affect autonomy and control in the same or similar work positions. The study expands the existing literature on autonomy and control (i.e., LOC and the job characteristics model) and increases the understanding of innovation and its obstacles in a retail context. The study highlights the importance of managers understanding employees' LOC construction and job characteristics in retail trade, which may lead to job redesign and positive growth in staff members' working lives.